A Mississippian Mace at Iroquoia's Southern Door. Issue 1 (January 2015) - Giles, Bretton T.; Knapp, Timothy D.
Abstract : This paper documents a Mississippian chipped stone mace, found by Lyle Edger, an amateur collector, in an agricultural field in Nichols, NY, along the Susquehanna River. This crown-form mace is made out of Dover chert and was probably produced by Mississippian people who lived in Middle Tennessee, circa A.D. 1200–1400. We argue that the Nichols Mace could have been acquired by Iroquoian people as the result of either a gift or diplomatic negotiations. We conclude that the meanings the mace held for Iroquoian people were likely tied to how they acquired it.